2019
DOI: 10.1016/j.devcel.2019.04.018
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Hyaluronan Is a Hippo Pathway Ligand Directing Cell Density-Dependent Growth Inhibition via PAR1b

Abstract: High-molecular-weight hyaluronan, a major component of the extracellular matrix, is anti-oncogenic, whereas low-molecular-weight hyaluronan is prooncogenic, though the mechanisms underlying the size-dependent opposite bioactivities of hyaluronan remain uncertain. We show here that treatment with high-molecular-weight hyaluronan stimulates tumor-suppressive Hippo signaling in breast epithelial cells. Mechanistically, clustering of the CD44 extracellular domain by high-molecular-weight hyaluronan leads to recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 38 publications
2
65
0
Order By: Relevance
“…Loss of this normal HMWHA coating stimulates cell proliferation. Growth suppressive mechanisms of HMWHA are known to involve density-dependent Hippo pathway signaling as well as engagement of early contact inhibition through Ezrin-Radixin-Moesin (ERM) actin-binding proteins 49,50 . The buildup of perivascular HA in wildtype mice during hypoxia therefore serves to block medial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of this normal HMWHA coating stimulates cell proliferation. Growth suppressive mechanisms of HMWHA are known to involve density-dependent Hippo pathway signaling as well as engagement of early contact inhibition through Ezrin-Radixin-Moesin (ERM) actin-binding proteins 49,50 . The buildup of perivascular HA in wildtype mice during hypoxia therefore serves to block medial proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has recently been reported that MST1/2 (mammalian Ste20-like kinase 1/2), a component of the tumor-suppressing Hippo signaling pathway, is a novel substrate of PAR1b. 111 Therefore, further investigation may reveal the involvement of perturbed MST1/2-LATS1/2-YAP/TAZ signaling induced by the CagA-PAR1b complex in the pathobiological action of the CagA protein.…”
Section: Molecular Structure Of the Caga Proteinmentioning
confidence: 99%
“…1). For instance, the Hippo pathway is regulated by cell-cell contact 14,15) and cell polarity, [16][17][18] as well as by mechanical cues [19][20][21][22][23] such as extracellular matrix stiffness and traction forces exerted by neighboring cells. In addition to those physical cues, a general role of extracellular signaling pathways has become apparent, such as G-proteincoupled receptors [24][25][26][27] and the Wnt signaling pathway, [28][29][30][31] in the regulation of the Hippo pathway.…”
Section: Introductionmentioning
confidence: 99%